A reappraisal of the Pipeline embolization device for the treatment of posterior circulation aneurysms. (4th August 2014) - Albuquerque, Felipe C; Park, Min S; Abla, Adib A; Crowley, R Webster; Ducruet, Andrew F; McDougall, Cameron G
Abstract : Background: Use of the Pipeline embolization device (PED) in the posterior circulation is of some controversy. Objective: Recent publications have described adverse outcomes associated with the PED for vertebral and/or basilar artery pathology. We assessed our results in the treatment of this challenging subset of aneurysms after Food and Drug Administration (FDA) approval. Methods: We prospectively reviewed our series of PED cases in this cohort. Patients were assessed for aneurysm type, technical success, periprocedural complications, and aneurysm obliteration. Results: Since FDA approval, 17 patients with posterior circulation aneurysms were treated with the PED. These included aneurysms of the vertebral artery (V4) segments (n=8), basilar trunk (n=6), basilar apex (n=2), and cervical vertebral artery (n=1). Two patients had a prior subarachnoid hemorrhage. All of the aneurysms treated were either saccular, had a saccular component, or were dissecting in nature. No dolichoectatic aneurysms were treated. Technical success was achieved in all patients. One complication (1/17 patients; 5.9%), a parenchymal hematoma after ventriculostomy replacement, resulted in permanent disability. Angiographic follow-up has been obtained to date in 14 of the 17 patients and shows complete or near-complete (>90%) obliteration in all cases. Conclusions: Patient selection is essential for safe and effective PED treatment of posterior circulation aneurysms. The PED is equally effective in achieving aneurysm obliteration with an acceptable risk profile as it is in the anterior circulation. Dolichoectatic aneurysms were not included in this treatment cohort. PED may be a preferable alternative to open surgical treatment of posterior circulation aneurysms.